Richard T. Ely the story of economics in the United States - Warren J. Samuels (Emerald, 2002)
This work publishes for the first time Richard T. Ely's study of the history of American economic thought. Ely was both a reformer of economics and a leading economist between the 1880's and 1930's. A founder of the American economic association, he himself wrote on a vast number of topics. This history of American economics tells a story that is both straightforward and his own interpretation.
Keywords: Economics -- United States.; elektronické knihy; electronic books